PELAFALAN KOSA KATA BAHASA INGGRIS BIDANG PETERNAKAN MASYARAKAT DI DESA PENGOTAN - ARYANI, dkk., I G.AG. I. (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014, 2014)
This community service concerned with the English pronunciation of the community at Pengotan village, specifically related with Animal Science vocabulary. It aims to improve their English abilities as second language learners and convince them to be confident in communicating the language.Techniques of pronouncing words were given by using stimulus and response through drilling in the discussion and practices. Evaluation was carried out by observing 25 people who were involved concerning with their ability of pronouncing words. Result showed that mistakes occurred in pronouncing consonants in the labial articulation, such as: p, t, v, f, and s. Problems raised due to the limited of understanding that English should be intensively practised. It can be concluded that learning to pronounce english words should be motivated by the personal and confident is needed to have the capability. Besides, media of learning could be found widely in this era of technology. Keywords: pronunciation, words, drilling, stimulus and response